Private Equity and its Role in the Development of the Indian Manufacturing Sector - Uddin, Mohammad Ahmar; Jamil, Syed Ahsan; Khan, Khaliquzzaman (International Journal of Economics and Financial Issues, 2016)
Manufacturing sector accounts for only 16% of GDP in India, while in China it is around one third of its GDP. Also the share of Indian manufacturing in the worldwide markets is dismal at 1.4%, while China it is now 13% from just 2.9% in 1990s. India also aspires to have such growth in its manufacturing sector. Growth of manufacturing sector is vital due to its multiplier effect on economy and employment. Every job created in the manufacturing sector creates two-three additional jobs in related activities. The aim of the Indian National Manufacturing Policy (2011) is to create to 100 million jobs and increase the share of manufacturing in GDP to 25% by 2022. Private Equity as financial intermediaries improves the allocation of resources from the investors and also provides various types of managerial assistance to industry enabling make them to be more competitive. This paper emphasizes the role that can be played by Private equity in the development of Indian manufacturing sector. Also the paper highlights the various types of assistance and problems in private equity. Keyword: manufacturing, private equity, development, India JEL Classification: E66, G20, G23, L26, L60